Arrange The Factors to Improve Employees Performance in PT. XYZ by Using Fuzzy Logic Approach - Berlian Fatikh Mubaarok; Bambang Syairudin (IPTEK Journal of Proceedings Series, 2019)
The success of a company is often seen in the company's human resources. Increased employee performance is very important for human resource management in companies that assist individual development, improve organizational performance, improve employee productivity and for the achievement of long-term objectives of the company. This research proposes is going to suggest the factors to improve the employee's motivation and performance. The pattern of these factors can be used as one of supports to improve the employee's performance in PT.XYZ. PT.XYZ hasn’t “tools” yet to find and improve the employees performance. This study uses data from questionnaires with Likert scale and calculated by using relative importance index (RII) to determine the importance of fuzzy factor and logic to see the influence and prediction value of employee performance improvement level. The final result and this research get result of the possibility of employee performance improvement equal to 46,6% Factor to pay attention on employee performance is teamwork, this factor get very high valuation from employees